2018
DOI: 10.1186/s12888-018-1931-4
|View full text |Cite
|
Sign up to set email alerts
|

‘Suicide rates in Crete, Greece during the economic crisis: the effect of age, gender, unemployment and mental health service provision’

Abstract: BackgroundRecently, suicides in Greece have drawn national and international interest due to the current economic crisis. According to published reports, suicides in Greece have increased up to 40% and Crete has been highlighted as an area with the sharpest increase.AimTo investigate the suicide mortality rates in Crete between 1999 and 2013 and their association with the economic crisis.MethodsData on suicides were selected from the Department of Forensic Medicine files of the University of Crete.ResultsOur a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…An impact of occupational factors even when adjusted for factors at other levels is a particularly interesting finding for understanding suicide in the working‐age population. Studies usually focused on one or two particular levels (e.g., socioeconomic (Alicandro et al, 2019; Basta et al, 2018; Borrell et al, 2020; Bossard et al, 2016; Chan et al, 2014; Hagedoorn et al, 2020; Harper et al, 2015; Hiyoshi et al, 2018; Milner, Niven, et al, 2015; Vanderoost et al, 2013), social‐behavioral (Deckert et al, 2015; Gearing & Alonzo, 2018; Gil‐Lacruz et al, 2019; Stack & Laubepin, 2019; Torgler & Schaltegger, 2014; Tsai et al, 2014) or occupational level (Alexopoulos et al, 2016; Bossard et al, 2016; Cohidon et al, 2010; Encrenaz et al, 2016; Guseva Canu et al, 2019; Hawton et al, 2011; Klingelschmidt et al, 2020; McIntosh et al, 2016; Milner et al, 2014; Milner, Smith, et al, 2015; Milner et al, 2013; Mustard et al, 2010; Ringgenberg et al, 2018; Roberts et al, 2013; Stark et al, 2006; Tanaka et al, 2017; Wada et al, 2016)) and might have over‐ or underestimated their respective contributions.…”
Section: Discussionmentioning
confidence: 99%
“…An impact of occupational factors even when adjusted for factors at other levels is a particularly interesting finding for understanding suicide in the working‐age population. Studies usually focused on one or two particular levels (e.g., socioeconomic (Alicandro et al, 2019; Basta et al, 2018; Borrell et al, 2020; Bossard et al, 2016; Chan et al, 2014; Hagedoorn et al, 2020; Harper et al, 2015; Hiyoshi et al, 2018; Milner, Niven, et al, 2015; Vanderoost et al, 2013), social‐behavioral (Deckert et al, 2015; Gearing & Alonzo, 2018; Gil‐Lacruz et al, 2019; Stack & Laubepin, 2019; Torgler & Schaltegger, 2014; Tsai et al, 2014) or occupational level (Alexopoulos et al, 2016; Bossard et al, 2016; Cohidon et al, 2010; Encrenaz et al, 2016; Guseva Canu et al, 2019; Hawton et al, 2011; Klingelschmidt et al, 2020; McIntosh et al, 2016; Milner et al, 2014; Milner, Smith, et al, 2015; Milner et al, 2013; Mustard et al, 2010; Ringgenberg et al, 2018; Roberts et al, 2013; Stark et al, 2006; Tanaka et al, 2017; Wada et al, 2016)) and might have over‐ or underestimated their respective contributions.…”
Section: Discussionmentioning
confidence: 99%
“…It can, therefore, be observed that in the Greek population this suicide method is practiced by older age groups. Furthermore, various studies concerning the impact of economic austerity on the suicide rates in Greece noted a significant increase in suicides committed by the middle‐aged and the elderly and found unemployment to correlate with suicide rates of males aged 20–24, 50–54, and 60–64 years ( p < 0.001), probably because middle‐aged men traditionally carry the main burden of the economic well‐being of the family (6,39).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies reported increased suicide rates during recession periods, other failed to replicate them. 26,[42][43][44][45] A comprehensive study investigated suicide trends at a global level for the years 2000 to 2007 and for the year 2009, collecting data from 27 European and 27 non-European countries (these latter included 18 American, 8 Asian countries, and 1 African country). 14 An increase in suicide rate was noted after 2008 especially in men in the United States and in countries with higher levels of job loss.…”
Section: Suicidementioning
confidence: 99%
“…Finally, the bigger increase in suicides was registered in Eastern Crete, suggesting the impact of the lack of mental health services in that region. 45 In the United Kingdom, a study reported an increase in suicides, especially among men, in the years following the beginning of the economic crisis. The increase in suicides affected the regions characterized by the biggest rises in unemployment.…”
Section: Suicidementioning
confidence: 99%